CaMKIIdelta subtypes: localization and function - Gray, Charles B.; Heller Brown, Joan (Frontiers in Pharmacology, 2014)
In this review we discuss the localization and function of the known subtypes of calcium/calmodulin dependent protein kinase IIδ (CaMKIIδ) and their role in cardiac physiology and pathophysiology. The CaMKII holoenzyme is comprised of multiple subunits that are encoded by four different genes called CaMKIIα, β, γ, and δ. While these four genes have a high degree of sequence homology, they are expressed in different tissues. CaMKIIα and β are expressed in neuronal tissue while γ and δ are present throughout the body, including in the heart. Both CaMKIIγ and δ are alternatively spliced in the heart to generate multiple subtypes. CaMKIIδ is the predominant cardiac isoform and is alternatively spliced in the heart to generate the CaMKIIδB subtype or the slightly less abundant δC subtype. The CaMKIIδB mRNA sequence contains a 33bp insert not present in δC that codes for an 11-amino acid nuclear localization sequence. This review focuses on the localization and function of the CaMKIIδ subtypes δB and δC and the role of these subtypes in arrhythmias, contractile dysfunction, gene transcription, and the regulation of Ca2+ handling.